Prophylactic use of tranexamic acid to reduces blood loss and transfusion requirements in caesarean section - Sunda, Urmila; Bhadana, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Postpartum haemorrhage (PPH) is most dreaded complication which occurs worldwide, more prevalent in developing countries after both vaginal and caesarean delivery. Prophylactic administration of a uterotonics immediately after delivery is the only procedure that has been proved to reduce rates of postpartum haemorrhage. Tranexamic acid, an antifibrinolytic is recommended by WHO for management of PPH, its role to reduce blood loss in caesarean section as a prophylactic agent is not well studied. Methods: This study was conducted in a tertiary care hospital at New Delhi total 100 pregnant women with age ≥18 and <35 years and singleton alive fetus who underwent caesarean section were included for this study. Study population was divided in two group. Women assigned to the study group received 1 gm tranexamic acid slowly intravenously over 10 minutes after delivery of the baby as per existing unit protocol. Those women who received tranexamic acid was compared with other group who did not received tranexamic acid. The primary outcomes were mean blood loss (ml) and mean fall in hemoglobin level within 48 hours after surgery. Results: Amount of blood loss was significantly low (mean 369 ml) in tranexamic acid group as compared to control group (488 ml), the difference was statistically significant (p value 0.001). Mean fall in haemoglobin level was also low (1.17 mg/dl) in group who received tranexamic acid as compared to control group (1.87 mg/dl), the difference was statistically significant (p value 0.001). Postpartum hemorrhage (blood loss more than 1000 ml) was observed in 1 patient in control group and no case of PPH was observed in study group. Conclusions: Tranexamic acid administration prior to caesarean section was effective in reducing the blood loss intra and postoperative period, without any immediate maternal and neonatal adverse events as well as reduces the need of blood transfusion.